2022
DOI: 10.1021/acschembio.2c00411
|View full text |Cite
|
Sign up to set email alerts
|

Peptide–Antibody Fusions Engineered by Phage Display Exhibit an Ultrapotent and Broad Neutralization of SARS-CoV-2 Variants

Abstract: The spread of COVID-19 has been exacerbated by the emergence of variants of concern (VoC). Many VoC contain mutations in the spike protein (S-protein) and are implicated in infection and response to therapeutics. Bivalent neutralizing antibodies (nAbs) targeting the S-protein receptor-binding domain (RBD) are promising therapeutics for COVID-19, but they are limited by low potency and vulnerability to RBD mutations in VoC. To address these issues, we used naïve phage-displayed peptide libraries to isolate and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…Frontiers in Microbiology 06 frontiersin.org pathogen invasions in this lab (Zhao et al, 2012) or others (Hall et al, 2009;Wei et al, 2020). This study and several other efforts (Anand et al, 2021;Sokullu et al, 2021;Ballmann et al, 2022;Labriola et al, 2022;Petrenko et al, 2022;Sevenich et al, 2022;Yang et al, 2022) demonstrated that PhD was a plausible method for generating possible therapeutics to treat COVID-19 as well. For example, Petrenko used phage-displayed spike S1 protein mimotopes to search for "all" cellular receptors, including authentic and alternative ones.…”
Section: Synthetic C2 and C6 Peptides Blocked The Binding Of Spike-tr...supporting
confidence: 59%
“…Frontiers in Microbiology 06 frontiersin.org pathogen invasions in this lab (Zhao et al, 2012) or others (Hall et al, 2009;Wei et al, 2020). This study and several other efforts (Anand et al, 2021;Sokullu et al, 2021;Ballmann et al, 2022;Labriola et al, 2022;Petrenko et al, 2022;Sevenich et al, 2022;Yang et al, 2022) demonstrated that PhD was a plausible method for generating possible therapeutics to treat COVID-19 as well. For example, Petrenko used phage-displayed spike S1 protein mimotopes to search for "all" cellular receptors, including authentic and alternative ones.…”
Section: Synthetic C2 and C6 Peptides Blocked The Binding Of Spike-tr...supporting
confidence: 59%
“…1 hour later cells were infected with SARS-CoV-2 at a multiplicity of infection (MOI) of 0.01 and cultured for 72 hours. Four strains were used: 1) the human 2019-nCoV strain 2019-nCoV/Italy-INMI1, isolated in Italy (ex-China) from a sample collected on January 29, 2020, kindly provided by the Istituto Lazzaro Spallanzani, Rome, Italy [ 19 ], 2) GZ69 (genomic data are available at EBI under study accession n. PRJEB38101), 3) Delta variant B.1.167.2 and 4) Omicron BA.1 variant, the last three viral strains kindly provided by the Department of Molecular and Translational Medicine, Section of Microbiology and Virology, University of Brescia Medical School, Brescia, Italy [ 20 23 ]. The 2019-nCoV/Italy-INMI1 strain was used for initial experiments and for drug combination studies, GZ69 was used as confirmatory strain as it was the main circulating variant in Italy at the time experiments were performed.…”
Section: Methodsmentioning
confidence: 99%
“…While combining separate RBD-directed antibodies into a single molecule using similar mAb design principles [ 73 ] represents a promising approach to withstand viral resistance, some of the broadest RBD-directed antibodies described to date that even recognize divergent sarbecoviruses [ 24 , 25 ] are evaded by recent Omicron sublineages [ 11 , 13 , 14 , 74 ]. Thus, additional strategies to further expand valency [ 75 ], target subdominant RBD epitopes [ 76 ] or other ‘cold spot’ regions of spike entirely—such as the highly conserved S2 stem helix [ 77 , 78 ]—and more rigorously analyze the potential for escape may be needed to generate more resilient coverage across current and future viral variants. We envision that a detailed analysis of the epitopic landscape, coupled with rational antibody design strategies, will make it possible to engineer ‘escape-proof’ mAbs in such a way that their neutralization potency need not be sacrificed for their neutralization breadth.…”
Section: Discussionmentioning
confidence: 99%